Model parameter extraction for obliquely propagating surface acoustic waves in infinitely long grating structures. (10th June 2016) - Tang, Gongbin; Han, Tao; Chen, Jing; Zhang, Benfeng; Omori, Tatsuya; Hashimoto, Ken-ya
Abstract: In this paper, we propose the use of the "longitudinal resonance condition" for the characterization of the two-dimensional propagation of surface acoustic waves (SAWs) in periodic grating structures, and also show a procedure for extracting parameters required in the behavior model from the full-wave analysis. The condition is given by β x p = π, where p is the grating period and β x is the wavenumber of the grating mode in the longitudinal direction ( x ). This is based on the fact that in conventional SAW resonators, acoustic resonances including transverse ones occur when β x is real but the longitudinal resonance condition is mostly satisfied. The longitudinal resonance condition is applied to a simple model, and the wavenumber β y in the lateral direction ( y ) is expressed as a simple function of the angular frequency ω. The full-wave analysis is applied for SAWs propagating in an infinite grating on a 128°YX-LiNbO3 substrate, and the anisotropy parameter γ is extracted by the fitting with the derived equation. The fitted result agrees well with the original numerical result. It is also indicated that γ estimated by this technique is significantly different from the value estimated without taking the effects of the grating structure into account.